Rework the conflict. "Bunker", a case of relational art - Cecilia De Carli (piano b, 2017)
The contribution deals with the theme of the conflict on his positive side of reworking through a case of relational art. This is the process developed by Laura Morelli and related to the bombardment of the Dalmine steelworks on the 16th of July 1944. Between 2006 and 2007 the artist faced the elaboration of what happened across an historical research and an artistic/relational project that involved groups of people who had suffered the loss of their loved ones and she worked on a collective restitution, later proposed to the public. The process of artistic transposition came to a huge impactful installation welcomed by the Dalmine steelworks. In 2016 the installation was rebuilt in the chapel S. Francesco of Università Cattolica in Milan capturing a new performance dimension compared to the multiple implications of the current conflict and in its elaboration.